PENERAPAN MANAJEMEN SEKURITI PADA PT FREEPORT INDONESIA : SURVEI SEKURITI, PRINSIP-PRINSIP KEAMANAN, ANCAMAN DAN MANAJEMEN RESIKO - M. Al Afif Annasai; Edy Soesanto, Novializa Ramadhayanti, Mochamad Refa Mulya Dewa (CV. Adiba Aisha Amira, 2024)
PT. Freeport Indonesia is a subsidiary of Freeport-McMoran Copper & Gold Inc and operates in Indonesia based on a Contract of Work signed in 1967. The operations of PT. Freeport in Indonesia shows that the Government has given legal authority to PT. Freeport to carry out mining has fulfilled the requirements for company operations based on the laws in force in Indonesia (Yoesry, 2019). Security management is an important step to carry out security efforts and prevent losses from disturbances that can result in losses effectively and efficiently. This research uses qualitative data analysis. Simply put, the data analysis method used is a method that focuses on explanations and terms and does not include numbers.